MUSCULOSKELETAL DISORDERS RISK ASSESSMENT AMONG SMALL TOFU FACTORY WORKERS IN TANGERANG CITY: AN INDONESIAN CASE STUDY - Viatina, Kania; Tejamaya, Mila; Widanarko, Baiduri (Universitas Airlangga, 2024)
Introduction: Conventional tofu production involves various manual handling tasks which increases the risk of musculoskeletal disorders (MSDs). A previous study found a very high risk of MSDs in tofu manufacturing, especially in the filtering task with a REBA score of 13. Aims: This study aims to evaluate the risk of MSDs in tofu factory workers. Methods: Workplace observations and unstructured interviews were conducted at two traditional tofu factories (X and Y) and a more modern silken tofu factory to identify the risk of MSDs. The Nordic Musculoskeletal Questionnaire and the Quick Exposure Check (QEC) method were used to determine the prevalence and risk of MSDs. A total of 52 workers voluntarily participated in this study. Results: The traditional and silken tofu manufacturing processes involved seven and fifteen tasks, respectively. This study found that workers in the traditional tofu factories had a higher prevalence of MSDs than those in the silken tofu factory. In the past 12 months, traditional tofu factory workers reported MSDs in their lower back (94.4%), right shoulder (77.8%), and neck (61.1%). On the other hand, silken tofu factory workers reported MSDs in their lower back (81.3%), right shoulder (62.5%), and upper back region (56.3%). According to the QEC method, grinding and filtering were identified as two tasks with a very high risk of MSDs in the traditional factories. In addition, transferring tofu crates from cold water to hot water tub in the silken factory was identified as a very high risk of MSDs. Conclusion: Intervention is necessary for tasks with a very high risk of MSDs in small tofu factories.